Convocation 2009 (Institutional Knowledge at Singapore Management University, 2009)
Enjoying the address by Dato' Sri Tony Fernandes, Group CEO of AirAsia, at Singapore Management University's tenth convocation. Left to right: Deputy President Tan Chin Tiong, Chairman Ho Kwon Ping, Chancellor Richard Hu, President Howard Hunter and Provost Rajendra Srivastava. Convocation 2009 was held at Suntec City Convention Centre on 15 August 2009.